PENGARUH ISLAMIC BRANDING DAN PERSEPSI KEMUDAHAN TERHADAP MINAT INVESTASI EMAS DIGITAL MAHASISWA STAI ALI BIN ABI THALIB SURABAYA - Sirajul Siraj; Umbu Aha; Andy Fahmi; Muhammad Nafis (LPPM STAI Muhammadiyah Probolinggo, 2026)
Financial digitalization has driven the rise of application-based investment instruments, including digital gold. For students in Islamic higher education, financial decisions are driven not only by technological functionality but also by Sharia compliance. This study aims to analyze the partial and simultaneous effects of Islamic Branding and Perceived Ease of Use on Interest in Digital Gold Investment among students at STAI Ali bin Abi Thalib Surabaya. A quantitative associative approach was employed with 132 active students selected via simple random sampling. Data gathered through structured Likert-scale questionnaires were analyzed using multiple linear regression analysis. The results indicate that partially, both Islamic Branding (t = 8.221; p = 0.000) and Perceived Ease of Use (t = 5.942; p = 0.000) have a positive and significant effect on investment interest. Simultaneously, both variables significantly influence interest (F = 106.2; p = 0.000) with an contribution of 62.2%. Strikingly, Islamic Branding emerged as the most dominant factor, although descriptive data recorded critical student skepticism regarding interest-free operations. This study underscores that for educated Islamic consumers, Sharia legality serves as a primary filter before technical ease. Therefore, the Sharia fintech industry must enhance contractual transparency to bridge the gap between financial convenience and religious compliance.